A Novel, Orally Delivered Antibody Therapy and Its Potential to Prevent Clostridioides difficile Infection in Pre-clinical Models - Roberts, April K.; Harris, Hannah C.; Smith, Michael; Giles, Joanna; Polak, Oktawia; Buckley, Anthony M.; Clark, Emma; Ewin, Duncan; Moura, Ines B.; Spitall, William; Shone, Clifford C.; Wilcox, Mark; et al. (Frontiers in Microbiology, 2020)
Clostridioides difficile infection (CDI) is a toxin-mediated infection in the gut and a major burden on healthcare facilities worldwide. We rationalised that it would be beneficial to design an antibody therapy that is delivered to, and is active at the site of toxin production, rather than neutralising the circulating and luminal toxins after significant damage of the layers of the intestines has occurred. Here we describe a highly potent therapeutic, OraCAb, with high antibody titres and a formulation that protects the antibodies from digestion/inactivation in the gastrointestinal tract. The potential of OraCAb to prevent CDI in an in vivo hamster model and an in vitro human colon model was assessed. In the hamster model we optimised the ratio of the antibodies against each of the toxins produced by C. difficile (Toxins A and B). The concentration of immunoglobulins that is effective in a hamster model of CDI was determined. A highly significant difference in animal survival for those given an optimised OraCAb formulation versus an untreated control group was observed. This is the first study testing the effect of oral antibodies for treatment of CDI in an in vitro gut model seeded with a human faecal inoculum. Treatment with OraCAb successfully neutralised toxin production and did not interfere with the colonic microbiota in this model. Also, treatment with a combination of vancomycin and OraCAb prevented simulated CDI recurrence, unlike vancomycin therapy alone. These data demonstrate the efficacy of OraCAb formulation for the treatment of CDI in pre-clinical models.